Antecedents and consequences of organizational politics: a select study of a central university. Issue 3 (7th November 2016) - Mishra, Poonam; Sharma, Shiv Kumar; Swami, Sanjeev
Abstract : Purpose: The purpose of this paper is to investigate the relationship between perceived organizational politics and three levels of antecedents (i.e. organizational, work environment and individual levels) and its consequents. It further aims to examine the relative importance of the three levels of antecedents in influencing employees' POP. The study has been conducted at a central university in India. Design/methodology/approach: A conceptual framework and a set of hypotheses were first developed on the basis of a review of previous studies of organizational politics (OP). A questionnaire was then developed, carrying 55 items related to eight constructs and the demographic characteristics of its respondents. Judgmental sampling was used to choose the university. The respondents were selected on the basis of convenience. Primary data were collected via a structured questionnaire from 45 faculty members at the university. The sample was made up of professors, associate professors and assistant professors from its various departments. To test the hypotheses, data were analyzed using partial least squares structural equations modeling (PLS-SEM). Findings: The results have indicated that all the three levels of antecedents have significant impacts on POP. The antecedents of workforce diversity (the organizational level), relationship conflict (the work environment level) and a need for power (the individual level) have a significant positive impact on POP. No relationship was found between role conflict and POP. Of the three levels of antecedents, it was observed that the organizational level contributed most significantly to POP. Of the three consequences, the intention to turnover and job anxiety were found to be positively related to POP, while organizational commitment was negatively related to it. Practical implications: The study provides managerial insights for both organizations and managers. Workforce diversity is a primary driver of POP and it is under the purview of organizations. Thus, to control the unfavorable consequences of POP, organizations must design effective policies to manage workforce diversity. Specifically, human resource processes must be formalized. Since human managers often make decisions in favor of those who are relatively homogeneous to them (homosocial reproduction), the distribution of resources and benefits is restricted to a few people only. Those who do not get their share of organizational resources perceive such acts of homosocial reproduction to be political. If policies are formalized, people have to take decisions within the boundaries of well-defined sets of rules and procedures. Those who are not homogeneous with decision-makers (the outgroup) should get a fair share of organizational resources in such a formalized environment. They neither need to play political games to gain power, nor will they perceive the organizational processes and environment to be political. It is also suggested that managers design effective development programs for enhancing the political skills of "outgroups" and minorities. This would help them to understand how to deal with political situations. Thus, the detrimental effects of employees' political perceptions on work-related outcomes would be reduced. Originality/value: Although a large number of studies on the antecedents and consequents of POP have been reported, the antecedents and consequences mentioned herein have never been examined previously by a single study. Four antecedents are introduced at three levels. Furthermore, in previous research, the relationships examined have treated OP either as a dependent variable or an independent variable. However, for this paper, the authors have provided a PLS-SEM-based model, which allows for simultaneous treatment of organizational politics as an independent variable in some relationships, and as a dependent variable in other relationships.